Development Strategy of Perumda Tirta Musi in Serving Palembang City's Drinking Water Needs - Juliando Saragih; Yusman Syaukat; Hendro Sasongko (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Perumda Tirta Musi, as a Regional-Owned Enterprise (BUMD) representing the Palembang City Government, plays a crucial role in meeting the city's drinking water needs. However, the company has not yet achieved the drinking water service coverage and profit targets outlined in its business plan and Regional Medium-Term Development Plan. This study aims to: (1) analyze the trend of Perumda Tirta Musi's drinking water service performance in Palembang City, and (2) formulate a development strategy for Perumda Tirta Musi to serve water needs in Palembang City. This research uses trend analysis to evaluate the performance of Perumda Tirta Musi and uses the IFE, EFE, IE, SWOT, and QSPM matrices to formulate the development strategy of Perumda Tirta Musi. The results indicated that Perumda Tirta Musi needs to pay attention to the achievement of the cash ratio, customer water flow hours, customer water pressure, water meter turnover, and the increasing trend of water loss. The company development strategy that can be carried out by Perumda Tirta Musi is to improve the distribution network connectivity/integration between service areas. The next priority strategy that can be carried out is to increase production/service capacity in potential areas of residential growth. These prioritized strategies offer actionable considerations for Perumda Tirta Musi's management as they strive to enhance drinking water services in Palembang City. Keywords: Strategic Management, Performance, Drinking Water, SWOT, QSPM